Tingkat Kesulitan Soal Buatan Guru Bidang Studi Matematika Menurut Teori Tes Klasik pada Tingkat SMP di Kota Baubau - Rasmuin Rasmuin; Sukra Luddin (Jurnal Akademik Pendidikan Matematika, 2022)
Objective of this research was to analysis and to describe the level of difficulty of the test made by the teacher in the field of Mathematics subject according to the Classical Test Theory at the Junior High School level in Baubau City. Type of this research was quantitative research with descriptive method. The research was carried out at 7 (seven) State Junior High Schools in Baubau City, with the research subjects being the entire multiple choice test package made by the teacher for the Final Semester Examination (UAS) even in the field of Mathematics for class VIII students in the 2020/2021 academic year. The data in this research were collected using documentation technigues. Based on the results of the research and discussion, it could be concluded that the level of difficulty of the UAS test questions for the 2020/2021 academic year made by teacher in the filed of Mathematics subject according to the classical test theory at 7 (seven) public Junior High Schools in Baubau City, namely SMP Negeri 2 Baubau there were 37,5% categories very difficult, 5% in the difficult category, and 57,5% in the medium category, with an average of 0,287. SMP Negeri 4 Baubau had 15% difficult category, 80% medium category, and 5% easy category, with an average of 0,458. SMP Negeri 6 Baubau had 65% difficult category and 35% medium category with an average of 0,283. SMP Negeri 8 Baubau there were 48% difficult category and 52% medium category, with an average of 0,269. SMP Negeri 10 Baubau had 50% difficult category and 50% medium category, with an average of 0,341. SMP Negeri 16 Baubau had 6,7% very difficult category, 60% difficult category, and 33,3% moderate category, with an average of 0,283. SMP Negeri 18 Baubau contained 14,3% in the difficult category, 14,3% in the medium category, and 71,4% in the easy category, with an average of 0,703.